Proteasome activity imaging and profiling characterizes bacterial effector syringolin A. - Kolodziejek, I; Misas-Villamil, J; Kaschani, F; Clerc, J; Gu, C; Krahn, D; Niessen, S; Verdoes, M; Willems, L; Overkleeft, H; Kaiser, M; van der Hoorn, R (2011)
Syringolin A (SylA) is a nonribosomal cyclic peptide produced by the bacterial pathogen Pseudomonas syringae pv syringae that can inhibit the eukaryotic proteasome. The proteasome is a multisubunit proteolytic complex that resides in the nucleus and cytoplasm and contains three subunits with different catalytic activities: β1, β2, and β5. Here, we studied how SylA targets the plant proteasome in living cells using activity-based profiling and imaging. We further developed this technology by introducing new, more selective probes and establishing procedures of noninvasive imaging in living Arabidopsis (Arabidopsis thaliana) cells. These studies showed that SylA preferentially targets β2 and β5 of the plant proteasome in vitro and in vivo. Structure-activity analysis revealed that the dipeptide tail of SylA contributes to β2 specificity and identified a nonreactive SylA derivative that proved essential for imaging experiments. Interestingly, subcellular imaging with probes based on epoxomicin and SylA showed that SylA accumulates in the nucleus of the plant cell and suggests that SylA targets the nuclear proteasome. Furthermore, subcellular fractionation studies showed that SylA labels nuclear and cytoplasmic proteasomes. The selectivity of SylA for the catalytic subunits and subcellular compartments is discussed, and the subunit selectivity is explained by crystallographic data.